Süreyya-Dani technique, a new technique to address notching of soft triangle and opening external nasal valve - Omer, Goran Latif; Şeneldir, Süreyya; Di Girolamo, Stefano; Habibullah, Imad J.; Ahmed, Avar F.; Ali, Sahand S.; Abdullah, Aland S.; Mustafa, Ayman M.; Abdalla, Berun A.; Hassan, Hemin Noori; Mohammed, Shvan H.; Kakamad, Fahmi H. (Frontiers in Surgery, 2024)
chief complaints were found among patients, with the majority 37(37%) expressing cosmetic concerns. A statistically significant difference was found for the association of nasal tip defects with genders, intraoperative findings, and chef complaints, and the association between the degree of external valve insufficiency and crural weakness (P-value<0.05).Despite many techniques that have been put forward to fix narrowed nasal valves and prevent notching of the soft triangle, the Süreyya-Dani Technique could work to prevent its occurrence successfully.